Heterogeneous health profiles and healthcare utilization of the middle-aged and elderly with multiple health insurance schemes in China. (May 2019) - Ye, L.; Shia, B.-C.; Fang, Y.; Lee, T.-S.
Abstract: Objectives: China is facing an escalating demand of healthcare services from the middle-aged and elderly. Compared with the traditional view of health on symptoms and diseases, this study aimed to assess the heterogeneous health profiles of middle-aged and elderly Chinese by a person-centered approach. Furthermore, this study examined the effects of health profiles and associated factors on healthcare utilization within the context of China's multiple health insurance schemes. Study design: The study used the 2015 data of China Health and Retirement Longitudinal Study, a nationwide population-based sample of people aged 45 years and older. Methods: Latent class analysis (LCA) was adopted to identify the heterogeneous health profiles. Two-part models were adopted to assess the effects of associated factors on healthcare utilization. Results: Among 15, 250 Chinese aged 45 years and older, six heterogeneous health profiles were identified and labeled as 'Quite Healthy', 'Relatively Healthy', 'Comprehensive Comorbidities', 'Functional Impairment', 'Severe Disability', and 'Relatively Frail'. The Relatively Frail profile was the heaviest healthcare user. The Severe Disability profile took the least use of outpatient services but had relatively high utilization of inpatient services and outpatient expenditure. The Comprehensive Comorbidities profile tended to have the smallest effect on the frequency of visits for both inpatient and outpatient services, but its effect on outpatient expenditure was high. After controlling for health profiles, the significant effects of different health insurance programs on healthcare utilization were discussed. Conclusions: Introducing health profiles by the person-centered approach of LCA has provided a holistic understanding of complex healthcare demands for middle-aged and elderly Chinese. It is valuable for policy makers to improve healthcare resource allocation targeted for the middle-aged and elderly. Highlights: Heterogeneous health profiles were assessed by a person-centered approach. Six health profiles for middle-aged and elderly Chinese were identified. How health profiles and other factors impact healthcare utilization was evaluated. Significant effects of different health insurance were evaluated by controlling health profiles.